Halophytes As Bioenergy Crops - Sharma, Rita; Wungrampha, Silas; Singh, Vinay; Pareek, Ashwani; Sharma, Manoj K. (Frontiers in Plant Science, 2016)
Shrinking arable land due to soil salinization and, depleting fresh water resources pose serious worldwide constraints to crop productivity. A vision of using plant feedstock for biofuel production can only be realized if we can identify alternate species that can be grown on saline soils and therefore, would not compete for the resources required for conventional agriculture. Halophytes have remarkable ability to grow under high salinity conditions. They can be irrigated with seawater without compromising their biomass and seed yields making them good alternate candidates as bioenergy crops. Both oil produced from the seeds and the lignocellulosic biomass of halophytes can be utilized for biofuel production. Several researchers across the globe have recognized this potential and assessed several halophytes for their tolerance to salt, seed oil contents and composition of their lignocellulosic biomass. Here, we review current advances and highlight the key species of halophytes analyzed for this purpose. We have critically assessed the challenges and opportunities associated with using halophytes as bioenergy crops.